FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP DAN INTENSI PEMBELIAN KEMBALI KONSUMEN PADA LAYANAN ONLINE FOOD DELIVERY (OFD) DI INDONESIA - Hesti Cahya Yustika; Subagiyo (Jurnal Satya Mandiri Manajemen dan Bisnis, 2022)
Online Food Delivery (OFD) services are a popular method in Indonesia for ordering food and drinks compared to other methods such as by telephone, restaurant mobile applications, and restaurant websites. OFD service transactions in Indonesia are growing rapidly and are increasingly popular compared to before the COVID-19 pandemic. The purpose of this study was to determine the structural influence between variables which include hedonic motivation, time saving orientation, price saving orientation, prior online purchase experience, information fit-to-task, visual appeal, convenience motivation, post-usage usefulness, attitude, and repurchase. intention on OFD services in Indonesia. This research refers to the theory of planned behavior, technology acceptance model, and partial adoption of the extended information technology continuance model. This research was also conducted to determine changes in consumer behavior in using OFD services before and during the COVID-19 pandemic in Indonesia. In this study, data was collected from 207 users of GoFood or GrabFood services and processed using Structural Equation Modeling (SEM) on the LISREL 8.54 software. The results showed that eight of the sixteen hypotheses proposed had a significant effect. Price saving orientation, time saving orientation, and prior online purchase experience significantly have a positive effect on convenience motivation. Time saving orientation, prior online purchase experience, and convenience motivation have a significant positive effect on post-usage usefulness. Post-usage usefulness has a significant positive effect on consumer attitudes and repurchase intentions for OFD services. This research shows that after the COVID-19 pandemic ends, 28.50% of respondents will increase the frequency of purchasing food and beverages through OFD services, 29.47% of respondents will reduce it, and the rest with a fixed frequency.